PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN PENDEKATAN PMR TERHADAP ASPEK AFEKTIF MATEMATIKA SISWA KELAS VIII SMP NEGERI DI KABUPATEN LAMPUNG UTARA - Karsoni Berta Dinataa (Eksponen, 2019)
The purpose of this study was to determine the effect of the jigsaw cooperative learning model with a realistic mathematics education (PMR) approach to students' affective aspects of mathematics. This type of research is quasi-experimental research. This study consisted of independent variable namely jigsaw cooperative learning model with realistic approach and one dependent variable namely the affective aspects of students' mathematics. The population in this study was the eighth grade students of State Junior High Schools in North Lampung Regency. Sampling was carried out by stratified cluster random sampling technique and obtained 9 classes from 3 state junior high schools in North Lampung Regency, consisting of 3 experimental classes I, 3 experimental classes II, and 3 control classes. The instrument for collecting data is a questionnaire on the affective aspects of mathematics, Testing the hypothesis in this study using a t-test. The results showed that there was an influence of the Jigsaw cooperative learning model with the PMR approach to the affective aspects of students'mathematics.